Rancangan Strategi Komunikasi Pemasaran untuk Meningkatkan Eksistensi KOPTI Kota Bandung - Ami Purnamawati; Eksa Mulyani (LPPM Universitas Koperasi Indonesia, 2025)
The producer cooperative supplying soybeans called Kopti Kota Bandung is a multipurpose cooperative. Its business units face some issues and one of is unoptimized marketing communication strategy causing member participation declining and its existence in wider community getting lesser. The purposes of the research were both to describe the implemented marketing communication and to design fit marketing communication strategies that can be applied in enhancing the presence of Kopti Kota Bandung. Using a case study approach, data obtained through observation, interviews, and literature study were analyzed descriptively. The results of this research depict the marketing communication processes that occur at Kopti both offline and online. Subsequently, the research outcomes take the form of a design for marketing communication strategies that can be implemented by Kopti in both online and offline contexts, utilizing social media as well as print and electronic media. These marketing communication strategies aim to enhance the presence of Kopti Kota Bandung and members can participate more actively, and the existence of Kopti Bandung is going to be more widely recognized.